2020
DOI: 10.1126/scitranslmed.aaz3577
|View full text |Cite
|
Sign up to set email alerts
|

Neoantigen responses, immune correlates, and favorable outcomes after ipilimumab treatment of patients with prostate cancer

Abstract: Tumors with high mutational burden (TMB) tend to be responsive to immune checkpoint blockade (ICB) because there are neoantigens available for targeting by reinvigorated T cells, whereas those with low TMB demonstrate limited clinical responses. To determine whether antigen-specific T cell responses can be elicited after treatment with ICB in cancers that have a low TMB, we conducted a clinical trial with ipilimumab in 30 patients with metastatic castration-resistant prostate cancer. We identified two distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 36 publications
3
93
0
Order By: Relevance
“…ICB and PVSRIPO immunotherapy engage antitumor T cell immunity 3 . Immunologically active tumors are a feature of ICBresponsive patients in other indications 14 , in some cases in patients with low TMB 18 , and very low TMB associates with increased tumor-intrinsic inflammation in rGBM (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ICB and PVSRIPO immunotherapy engage antitumor T cell immunity 3 . Immunologically active tumors are a feature of ICBresponsive patients in other indications 14 , in some cases in patients with low TMB 18 , and very low TMB associates with increased tumor-intrinsic inflammation in rGBM (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…Relevant patient demographics, as well as survival information (updated as of April 29, 2020), are presented in Supplementary Table 1. Additional de-identified cohorts from previously published studies include: the MSKCC IMPACT study containing GBM patients treated with either αPD1 or αPD-L1 (in two cases with combined αCTLA4) 8 , αPD1-treated rGBM cohort (Zhao et al 10 ) 18 , the Glioma Longitudinal AnalySIS (GLASS) consortium 11 , Wang et al 16 , and TCGA.…”
Section: Methodsmentioning
confidence: 99%
“…No differences in terms of TMB and neoantigens were found between the immune and non-immune classes in our study. Although the somatic mutation frequencies of prostate cancer are dramatically lower than those in melanoma [55], Subudhi et al [56] reported that some metastatic castration-resistant prostate cancer patients who received ipilimumab treatment can still benefit from immunotherapy, with a median number of nonsynonymous somatic mutations of 76.…”
Section: Accepted Articlementioning
confidence: 99%
“…Finally, we looked at human clinical trial data from patients with metastatic prostate cancer treated with ipilimumab (anti-CTLA-4) on a single institution clinical trial (NCT02113657; ref. 47). Published RNA expression data were used to look at RARRES2, PTEN, and PD-L1 (CD274) in these patients, and evaluate clinical outcomes.…”
Section: Expression Of Chemerin In the Tme Leads To Decreased In Vivomentioning
confidence: 99%